Pengaruh Budaya Sekolah Terhadap Hasil Belajar Peserta Didik MIN 2 Hulu Sungai Tengah - Ubaidillah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research is motivated by the importance of school culture in improving the quality of education, particularly in shaping student character and learning outcomes. School culture, which encompasses the values of discipline, religiosity, responsibility, and positive habits, is believed to create a conducive learning environment. At MIN 2 Hulu Sungai Tengah, school culture has been implemented through various habituation activities such as prayer before and after lessons, congregational prayer, and the implementation of time discipline. However, it remains to be seen how this school culture influences student learning outcomes. This research used a quantitative approach with a correlational approach. Data collection techniques included observation, interviews, and documentation. Observations were used to observe the implementation of school culture within the madrasah environment. Interviews were conducted with the principal, teachers, and students to obtain more in-depth data. Documentation was used to obtain data on student learning outcomes and school activities that supported the research. Data were analyzed descriptively to determine the influence of school culture on student learning outcomes. The results showed that school culture at MIN 2 Hulu Sungai Tengah. (1) A school culture implemented through the habituation of religious activities, discipline, teacher role models, and an orderly and conducive learning environment has been proven to shape students' learning attitudes better. (2) Students accustomed to this school culture tend to be more disciplined, active in learning, and have a higher level of responsibility for learning assignments. (3) Documentation results show that most students are able to achieve or even exceed the Minimum Completion Criteria (KKM), indicating an improvement in learning outcomes. This is evident in increased discipline, better learning attitudes, and the large number of students achieving the Minimum Completion Criteria (KKM). Thus, it can be concluded that the better the school culture implemented, the better the learning outcomes of students at MIN 2 Hulu Sungai Tengah.